Ecuador, Siglo XXI: Una nueva narrativa democrática - Uharte Pozas, Luis Miguel (Nómadas. Critical Journal of Social and Juridical Science, 2013)
As a consequence of the crisis of the neoliberal model in Ecuador and its “market democracy” at the beginning of the Twenty First Century, a new democratic narrative arose that has become hegemonic in the country. The purpose of this work is to identify the central discursive axes of the new democratic project, and work out which of these have been implemented by the Ecuadorian Government led by President Rafael Correa. The work also analyses the discursive arguments between the Government and a part of the left which crossed over to the opposition and the related theoretical dispute over the appropriation of the symbols of the new democratic narrative.
Keywords: democratic narrative; “buen vivir”; plurinational State; rights of the nature.